Reducing risk of Type 2 diabetes in HIV: a mixed‐methods investigation of the STOP‐Diabetes diet and physical activity intervention. Issue 10 (25th February 2019) - Duncan, A. D.; Peters, B. S.; Rivas, C.; Goff, L. M.
Abstract: Aim: To conduct a mixed‐methods feasibility study of the effectiveness and acceptability of an individualized diet and physical activity intervention designed to reduce the risk of Type 2 diabetes experienced by people living with HIV. Methods: Participants with impaired fasting glucose and HIV were invited to take part in a 6‐month diet and physical activity intervention. Individualized advice to achieve 10 lifestyle goals was delivered monthly. Diabetes risk was assessed pre‐ and post‐intervention by measurement of the glucose and insulin response to a 3‐h meal tolerance test. Six‐month change was analysed using paired t ‐tests. Research interviews exploring the acceptability of the intervention and factors influencing behaviour change were conducted with those who participated in the intervention, and those who declined participation. Results: The intervention ( n =28) significantly reduced the following: glucose and insulin, both fasting and postprandial incremental area under the curve (glucose 7.9% and 17.6%; insulin 22.7% and 31.4%, respectively); weight (4.6%); waist circumference (6.2%); systolic blood pressure (7.4%); and triglycerides (36.7%). Interview data demonstrated the acceptability of the intervention. However, participants expressed concern that deliberate weight loss might lead to disclosure of HIV status or association with AIDS‐related illness. The belief that antiretroviral medications drove diabetes risk was associated with declining study participation or achieving fewer goals. Conclusions: We have demonstrated the beneficial effects of a lifestyle intervention in mitigating the increased risk of Type 2 diabetes associated with HIV. Future interventions should be designed to further reduce the unique barriers that prevent successful outcomes in this cohort. What's new?: People living with HIV have a disproportionately high risk of Type 2 diabetes. Significant barriers to diet and lifestyle behaviour change exist within HIV, including stigma, isolation and body image challenges, which should be taken into consideration when designing diabetes prevention interventions. We have demonstrated that an individualized diet and physical activity intervention significantly reduced Type 2 diabetes risk in a cohort of adults who were HIV positive. Our qualitative data provided rich insight into the complexity of supporting healthful behaviour change in HIV, highlighting a range of factors that act to motivate individuals or prevent behaviour change.